Radio detection of cosmic-ray air showers with the OVRO-LWA: Status and future plans. - Romero-Wolf, Andrés; Monroe, Ryan; Hallinan, Gregg; Carvalho, Washington; Plant, Kathryn; Belov, Konstantin; Nelles, Anna; Eastwood, Michael; Anderson, Marin; D'Addario, Larry; Kocz, Jonathon; Woody, David (Proceedings of Science, 2019)
We present the successful radio frequency (30 - 80 MHz) self-triggered detection and identification of 10 high energy cosmic rays with Caltech's Owens Valley Radio Observatory Long Wavelength Array (OVRO-LWA). The core of the OVRO-LWA consists of 256 dual-polarization antennas that are approximately evenly spaced in a 200 m diameter disk with several outliers at longer distances. Based on this success we present future plans for an array covering a 2.5 km diameter area for measuring the flux and composition of cosmic rays in the 3×1016 eV - 1018 eV energy band.
CRIS-Team Scopus Importer:2023-08-15